2017
DOI: 10.1002/hep.29146
|View full text |Cite
|
Sign up to set email alerts
|

The animal naming test: An easy tool for the assessment of hepatic encephalopathy

Abstract: The S-ANT is an easily obtainable measure useful for the assessment of HE. (Hepatology 2017;66:198-208).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
3
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 45 publications
6
134
3
7
Order By: Relevance
“…The PHES ≤–4 was considered abnormal . Moreover, to support the diagnosis of MHE, all patients underwent the animal naming test, which assesses the maximum number of animals listed in 1 minute, as described . The assessors of MHE were blinded to patients’ pharmacological therapy.…”
Section: Methodsmentioning
confidence: 99%
“…The PHES ≤–4 was considered abnormal . Moreover, to support the diagnosis of MHE, all patients underwent the animal naming test, which assesses the maximum number of animals listed in 1 minute, as described . The assessors of MHE were blinded to patients’ pharmacological therapy.…”
Section: Methodsmentioning
confidence: 99%
“…However, this is highly dependent on the presence of the companion, familiarity of the patient to the clinician, as well as availability of time that is required for the practitioner to ask these questions. A recent study to better define grade 1 using the simple animal naming test has been published, which requires further validation in other centers to study its ability to define this grade . The deficiency in this knowledge was also highlighted by the relatively few respondents who ordered specialized testing for MHE to better define lower grades of HE.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the test for diagnosing HE was 96% and the specificity (per definition) was 100% when comparing test results of patients with clinically OHE and healthy controls in the validation study [6]: 22% of the patients without clinical signs of HE achieved abnormal results in the PHES battery and were classified as having MHE. Campagna et al [10] recently found abnormal PHES results in 42.7% of 295 patients with liver cirrhosis but no OHE [ n  = 50 (17%) had grade 1 HE, 76 (26%) had MHE].…”
Section: Minimal/covert Hepatic Encephalopathy: Psychometric Test Promentioning
confidence: 99%
“…After rough correction for age and education effects, the authors defined cut-off values for a (simplified) S-ANT score that, in their opinion, could be used for an estimation of a patients’ cognitive function. A score of ≥ 15 indicates a probability of about 80% that the subject has no cognitive dysfunction, a score of < 10 indicates the presence of encephalopathy with a probability of about 80% [10]. …”
Section: Minimal/covert Hepatic Encephalopathy: Psychometric Test Promentioning
confidence: 99%